2011
DOI: 10.1517/14656566.2011.618496
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatment of generalized anxiety disorder

Abstract: Efficacy for treatment of GAD has been established for several different drug classes. At present, based on clear efficacy and good tolerability, first-line treatment with either a selective serotonin reuptake inhibitor (SSRI) or a serotonin-norepinephrine reuptake inhibitor (SNRI) is indicated. If an initial, at least moderate, clinical response is achieved under antidepressant therapy, treatment should be at least continued for 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 72 publications
3
56
0
Order By: Relevance
“…Today practice guidelines suggest that in the acute phase of treatment, a single drug, typically an AD, is initiated with the expectation that it will be continued at least until symptoms resolve, and ideally for 12 months beyond symptom resolution [2,20]. The selective serotonin reuptake inhibitors (SSRIs) and the serotonin-norepinephrine reuptake inhibitors (SNRIs) are recommended as first-line pharmacotherapeutic options in the US and internationally, this despite the fact that BZs elicit a rapid anxiolytic response as they are highly lipophilic and are also commonly used as first-line treatment by many non-psychiatrists [21].…”
Section: General Approach To Treatment and Management Of Treatment Famentioning
confidence: 99%
See 3 more Smart Citations
“…Today practice guidelines suggest that in the acute phase of treatment, a single drug, typically an AD, is initiated with the expectation that it will be continued at least until symptoms resolve, and ideally for 12 months beyond symptom resolution [2,20]. The selective serotonin reuptake inhibitors (SSRIs) and the serotonin-norepinephrine reuptake inhibitors (SNRIs) are recommended as first-line pharmacotherapeutic options in the US and internationally, this despite the fact that BZs elicit a rapid anxiolytic response as they are highly lipophilic and are also commonly used as first-line treatment by many non-psychiatrists [21].…”
Section: General Approach To Treatment and Management Of Treatment Famentioning
confidence: 99%
“…Patients who continue to endorse residual symptoms after successful treatment (achievement of remission) are at increased risk of relapse and recurrence. This underscores the importance of continuing treatment beyond the resolution of symptoms [2,3,20].…”
Section: General Approach To Treatment and Management Of Treatment Famentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are generally in line with current practice, in which SSRIs are often the first-line treatment of a range of anxiety disorders. Another review in the United States assessed data from placebo-controlled clinical trials of BZDs, azapirones, antidepressants, and anticonvulsant and antipsychotic drugs, and concluded that patients with general anxiety disorder should receive either an SSRI or SNRI as firstline treatment (Reinhold et al, 2011).…”
Section: E Modulators Of Serotonergic and Noradrenergic Transmissionmentioning
confidence: 99%